The role of thoracic surgery in the management of mesothelioma: an expert opinion on the limited evidence. (2nd June 2016) - Bertoglio, Pietro; Waller, David A.
ABSTRACT: Surgery has a key role at different points in the management of Malignant Pleural Mesothelioma. Diagnosis with video assisted thoracoscopy offers excellent sensitivity and specificity and a direct view of the pleural cavity to verify the extent of the tumor. Nodal involvement can be assessed by mediastinoscopy and either talc pleurodesis or partial pleurectomy can be used for symptom control in advanced stage disease. Extra Pleural Pneumonectomy (EPP) and Extended Pleurectomy Decortication (EPD) are used to prolong survival although the benefit of radical surgery has not has been fully clarified; EPP failed to show its benefit in the MARS trial and EPD is currently under investigation in the MARS2 trial. More randomized prospective trial data are needed to fully understand the role of radical surgery in the treatment of pleural mesothelioma.